Informed consent process in clinical trials: development of a patient-reported questionnaire - Marta Ruiz de Hoyos; Elena Villamañán-Bueno; Emma Fernández de Uzquiano; Pilar Gómez-Salcedo; María Río-Durango; Jesús Frías-Iniesta (Farmacia Hospitalaria)
Objective: To develop a Spanish-language questionnaire aimed at evaluating patients’ perception of the way they are briefed and their consent is obtained prior to participating in clinical trials. The tool was conceived to evaluate the following aspects: patients’ personal experience, the way the informed consent process was implemented in practice, patients’ level of satisfaction with the process, and their level of understanding of the study itself.